Genetic variability and phylogenetic relationship establishes distinctness of Kaunayen chicken of Manipur - SHARMA, REKHA; SHARMA, PRIYANKA; AHLAWAT, SONIKA; SINGH, TH RANADHIR; VIJ, P K; VIJH, R K; TANTIA, M S (The Indian Journal of Animal Sciences, 2017)
Conservation of locally adapted indigenous livestock has become an important objective in sustainable animal breeding.The current study is first detailed analysis of the genetic diversity harboured by Kaunayen chicken of Manipur.The genotype data generated on 24 microsatellite markers was analysed to establish distinctness of Kaunayen from other registered poultry breeds of India. Large number of observed alleles (212) and heterozygosity (0.66) indicated high genetic diversity. Mean number of alleles observed in Kaunayen chicken were 8.83±0.31 and ranged between 4 (MCW250 and LEI174) and 15 (LEI120). Mean effective number of alleles was significantly less (4.11±0.38) than the observed number of alleles. The maximum observed heterozygosity (1.0) was observed in MCW262 locus and the minimum (0.368) in LEI166. The expected heterozygosity (0.706) was more than the observed heterozygosity (0.664±0.036) which points to heterozygote deficiency and was also reflected in positive FIS estimate (0.06) for the population. Non-significant heterozygote excess on the basis of Infinite allele model and Two-phase model in conjunction with mode-shift analysis test, indicated an absence of bottleneck. Phylogenetic reconstruction on the basis of genetic distance places Kaunayen chicken as a distinct population with respect to other poultry breeds of India. All analysis showed that a significant amount of genetic variation is maintained in Kaunayen chicken population and has appropriately been registered as the 17th chicken breed of India.